Model Komunikasi Keluarga Etnis Betawi dalam Memotivasi Pendidikan Tinggi dari Perspektif Anak - Maulina Larasati Putri; Vera Wijayanti Sutjipto; Marisa Puspita Sary (Program Studi Ilmu Komunikasi, 2021)
Communication in the family plays an important role in providing motivation for the development of children's education and in determining the continuation of higher education for children. This study aims to determine the communication model that exists in Betawi ethnic families in motivating higher education for children. This research is qualitative. Data were collected through interviews, literature study, and observation. The informants of this study consisted of six students who had parents with ethnic Betawi family backgrounds. Three informants lived in the DKI Jakarta area and three other informants lived in the Depok area. The results of this study indicate that the Betawi ethnic family communication model in an effort to motivate children to continue their education to a higher level is in accordance with the ABX model proposed by Newcomb and the Interactional model. In the ABX model from Newcomb, both parents and children consider higher education to be very important. Then, in the interactional model, communication that takes place in families with Betawi ethnic backgrounds takes place openly and reciprocally. This study suggests that communication built by parents has an impact on motivation in children which then affects children's behavior, especially in terms of education. Therefore, parents must develop a good communication environment with their children.Keyword : Communication of Family, Model of Communication, Motivation